Positive and Negative Creativity: Individual and Environmental Influences on Government and Private Employees - Suralaga, Fadhilah; Dewi, Mulia Sari; Tresniasari, Nia (TAZKIYA Journal of Psychology, 2021)
Research on creativity as an attitude, thinking ability, and creative behavior developed in the education sphere is profoundly related to positive things. Meanwhile, the research for negative creativity or the allegedly dark side of creativity is still very limited both in education and in the industrial world. This study examines the influence of internal factors (personality and intelligence) and external factors (organizational climate and organizational culture) on positive and negative creativity. The sample comprised 180 government employees in a ministry office and 150 private employees at a well-known insurance company in Jakarta. The results of this study show that for government employees, positive creativity mainly influenced by internal factors, namely the openness personality type, and none of the external factors affects. Simultaneously, negative creativity influenced by external factors, particularly the goal-oriented organizational climate, and none of the internal factors affects. On the other hand, private employees have various positive creativity influenced by internal factors (such as extraversion personality and neuroticism) and also external factors (the culture of cooperation and customer orientation). In contrast, negative creativity influenced by external factors of the organization, specifically the internal process that runs within the organization.